(3OQGSI bjGSjI ebGQfg dWQb JbOjQ GSJLGHI GdYQV hGdJfHD deMUhdi bUH GdScQ hGdbeM ai eUQs - (3ehS, eQGO Rci(B.s (2008)
(3hgPG GdHMK gh OQGSI bjGSjg jSJgOa GdebGQfg Hjf GdWQjbg GdeHGTQg ef NdGd JbOjQ OGdI GdGSJLGHg ddcejGJ GdefJLg ddJZjQGJ ddeDKQg YdjgG hGdWQjbI ZjQ GdeHGTQg ef MjK Cf GdcejGJ GdefJLg gi YHGQg Yf GdGfJGLjg eVQhHG ai GdeSGMg, hCf GdeJZjQGJ GdJi JMJhjgG GSJLGHI GdcejGJ GdefJLg eG gi GdGJLejY ddeJZjQGJ GdJi JMhjgG cdG ef OGdI GdGfJGLjg hOGdI GdeSGMg , ceG jSJgOa GdHMK CjVG JhVjM GdCSdhH GdCeKd ddJfHD HGSJLGHI GdRQGY hPdc ef NdGd GdebGQfgHjf GSJNOGe WQjbI GdeQHYGJ GdUZQi GdYGOjg hWQjbI GdeYGOdGJ GdJi JHOh ZjQ eQJHWg XGgQjG dJbOjQ gPG ddJfHD hdJMbjb gOa GdOQGSg Je GdMUhd Ydi HjGfGJ efThQg ef GdLgGR GdeQcRi ddJYHFI GdYGeI hGdGMUGA deMUhdi bUH GdScQ heMUhd GdaeM, hdbO LGA GNJjGQ gPjf GdeMUhdjf dGNJdGa ebOQI hSQYI GSJLGHI GdRQGY ddJZjQGJ ai GdeJZjQGJ GdJaSjQjg dcdG GdeMUhdjf,s
(3jMJhi Ydi eQGLY(B.s
(3edNU HGddZI GdEfLdjRjI(B.s
1
Keywords: (3bUH GdScQs -- (3EbJUGOjGJ(B.s; (3GdScQs -- (3EfJGLs -- (3eUQ(B.s; (3GdbeMs -- (3LhGfH EbJUGOjIs -- (3eUQs; (3GdbeMs -- (3EfJGLs